Teamwork as a prerequisite for the development and innovation of small and medium enterprises in Serbia - Micić, Ivana (Economic Outlook, 2024)
Effective teamwork is necessary for the success of any organization, whether it is a small startup or a large corporation. When team members work together toward a common goal, they can leverage their skills, knowledge, and resources to achieve extraordinary results that would not otherwise be possible. Teamwork Enables SMEs to leverage the skills, knowledge and resources of their team members to achieve their goals and compete in the marketplace. Therefore, the subject of research on teamwork in small and medium-sized enterprises is an important and relevant area of study. The aim of this research is to examine the role of teamwork in the development and innovation of small and medium enterprises in Serbia. The research aims to investigate the benefits of effective teamwork in small and medium-sized enterprises. The research hypothesis is: effective teamwork has a statistically significant effect on the development and innovation of small and medium-sized enterprises. Among the research methods, a questionnaire was used in order to better understand that teamwork is viewed as an important factor in the development and innovation of small and medium-sized enterprises.